2009
DOI: 10.1182/blood-2009-02-203372
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33 induces angiogenesis and vascular permeability through ST2/TRAF6-mediated endothelial nitric oxide production

Abstract: IntroductionAngiogenesis is a critical process in physiologic and pathologic conditions, including embryo development, wound healing, tumor progression, and inflammatory diseases. 1 Inflammation and angiogenesis are closely associated, and pathologic angiogenesis has been implicated in the development of chronic inflammatory diseases. Interplay between inflammation and angiogenesis is mediated largely by cytokines, chemokines, and growth factors. Some of these molecules, including vascular endothelial growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
220
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(245 citation statements)
references
References 48 publications
19
220
2
4
Order By: Relevance
“…It has been revealed that IL-33 can stimulate angiogenesis and cell growth via its receptor ST2 expressed in the effecting cells (20,46). In this study we have observed that ST2 was expressed in both the adenomatous/cancerous epithelium and microvessels, whether IL- LGD: Lower grade dysplasia.…”
Section: Discussionsupporting
confidence: 50%
“…It has been revealed that IL-33 can stimulate angiogenesis and cell growth via its receptor ST2 expressed in the effecting cells (20,46). In this study we have observed that ST2 was expressed in both the adenomatous/cancerous epithelium and microvessels, whether IL- LGD: Lower grade dysplasia.…”
Section: Discussionsupporting
confidence: 50%
“…In contrast, sST2 appears to act as a decoy receptor for IL-33, blocking myocardial and vascular benefits (10)(11)(12). IL-33 is also expressed in endothelial cells (ECs) (13)(14)(15)(16), in which it induces angiogenesis (17), expression of adhesion molecules, and inflammatory activation (18). Here we report the surprising finding that endothelial IL-33 from pressure overload induces a selective systemic response, potentially linking hypertension with circulating factors that can affect the vasculature and other organs.…”
mentioning
confidence: 82%
“…IL-33 is expressed in quiescent ECs, and IL-33 protein can be secreted in living cells after mechanical stress (9,(13)(14)(15)(16)(17). We therefore hypothesized that endothelial-derived IL-33 could represent a mechanism by which pressure overload of the myocardium can promote systemic inflammation, and thus we developed mice with conditional deletion of IL33.…”
Section: Significancementioning
confidence: 99%
“…Recent data suggest that IL-33 promotes angiogenesis and endothelial permeability involved in tumorigenesis (Choi et al, 2009). Expression of IL-33 has been observed in various organs including stomach and lung, as well as in cells including pancreatic cancer cells and activated macrophages (Carriere et al, 2007).…”
Section: Discussionmentioning
confidence: 99%